Association of the FRAIL scale with rehabilitation outcomes in the community hospital setting - Jeffrey Jiang; Audrey Yan Yi Han; Joel Goh (Singapore Medical Journal)
Introduction: Frailty is associated with adverse health outcomes and can be measured using the FRAIL scale. In Singapore, its use has been studied in tertiary hospitals but not in community hospitals. A tool to predict rehabilitation outcomes would allow for better risk stratification and allocation of resources. We aimed to determine whether the FRAIL scale is associated with rehabilitation outcomes in patients admitted to the community hospital setting, where post-acute care and rehabilitation are primarily delivered. Methods: This was a retrospective cohort study. The FRAIL scale was utilised to screen 560 older adults who were admitted to a community hospital for rehabilitation. Data were analysed to determine the relationship between baseline characteristics and frailty status, with rehabilitation outcome measures of absolute functional gain, rehabilitation effectiveness, rehabilitation efficiency, length of stay and discharge destination. Results: The combined score of the FRAIL scale showed significant negative association with absolute functional gain (P < 0.001), rehabilitation effectiveness (P < 0.001) and rehabilitation efficiency (P < 0.001), whereas it was positively associated with increased length of stay (P < 0.05) and a need for continued support in increased care settings (P < 0.001). Individual components of the FRAIL scale, in particular, the ‘fatigue’, ‘ambulation’ and ‘loss of weight’ components, appeared to be highly associated with rehabilitation effectiveness and efficiency, especially among pre-frail patients. Conclusion: The utility of the FRAIL scale as an indicator of frailty status and its association with rehabilitative outcomes in the post-acute care setting were demonstrated. Moreover, the FRAIL scale may better predict the rehabilitative progress of pre-frail patients.